Literatur Review Peran Pelatihan dalam meningkatkan kinerjaSDM di Masa Covid-19 - risma, dhea feby (Economics and Business Faculty UNUSIA, 2021)
Human Resources (HR) is one element that is very important for an organization in order to achieve the success of the organization's goals. In the present, during the COVID19 Pandemic, companies must have had a very difficult time achieving their goals, one of the reasons is due to the decline in the performance of human resources in the company which is the effect of this Pandemic. Therefore, companies must have additional strategies in order to survive during this Pandemic. Human resource training is one way to stay afloat. As a result of the current pandemic, HR performance is expected to remain stable or even improve, and this is where training comes into play. Research in the field of human resources is conducted using a literature review method, in which relevant books and scientific articles are consulted as a source of information for future studies in the field. Human resource performance during a pandemic could benefit greatly from training, and this study shows that training can help employees improve and develop while also adapting to the current Covid-19 conditions.